Constitution of the state of North-Carolina : together with the ordinances and resolutions of the Constitutional Convention, assembled in the city of Raleigh, Jan. 14th, 1868 (HeinOnline. World constitutions illustrated., 1868)
Constitution of the state of North Carolina, together with the Ordinance and Resolutions of the Constitutional Convention of 1868 and published in 1869 in Raleigh. This convention was required by the Reconstruction Act, and resulted in the enfranchisement of blacks and more power to the people and to the governor. It also provided for free public schools between the ages of six and twenty-one, as well as for state prisons and charitable institutions. Of note, it was not popular with the wealthier conservatives and those unhappy with the reconstruction demands.